4 - Politics of Natural Resource Management and Accountable Systems in the Delivery of Water Services in Uganda - Kanyamurwa, John Mary (Africa Development, 2021)
The political behaviour of public institutions exhibited in the management of critical natural resources influences the nature of service delivery. In particular, the character of such public organizations as regulators of natural resources, like water, impacts not only on what such management bodies do and their functionality, but also on the way they respond to public accountable systems. The latter systems refer to those formal and informal public frameworks that emphasize the need to ensure that water services are delivered effectively, efficiently, satisfactorily and in a sustainable manner. It is mostly the shortfalls in such accountable systems, as is the case in most developing countries’ cities, that prompts analysis of the role of politics in the relevant public organizations. Thus, this article is intended to explore pertinent issues particularly relevant to the interests, rational choices and calculations in the regulation of natural resource management and the modes in which they impact on accountable systems in Uganda. Using a descriptive and correlational research design, data were collected using questionnaires administered to 1,086 respondents from key stakeholders in Kampala Capital City Authority (KCCA). The findings indicate that political considerations by water managers mostly led to utility maximization of self- interest rather than serving public interest in terms of decisions which were characterized by minimal participation of lower-level employees and water consumers. The level of adherence to accountable systems was low, suggesting that managers in water provision services were working hard to satisfy their political masters rather than the clients they served. The political considerations that underlined the practices in water resource management significantly watered down the promotion of accountable systems, but also affected the efficiency of the National Water and Sewage Corporation (NWSC). The article concludes that politics in organizations promotes skewed management practices that ultimately undermine accountable systems in the provision of critical resources such as water at the expense of consumers and citizens. Public reforms that enhance the independence of public institutions charged with the provision of vital development resources, which also enhance accountable systems in the public interest, are the most appropriate policy response to this challenge.